Risk preferences in surrogate decision making - Batteux, Eleonore; Ferguson, Eamonn; Tunney, Richard J. (Hogrefe, 2017)
There is growing evidence that decisions made on behalf of other people differ from the decisions we make for ourselves because we are less affected by the subjective experience of their outcome. As a result, the decisions we make for other people can be more optimal. This experiment investigated surrogate decision making using a probability discounting task where participants made choices between risky and sure options. Psychological distance between the decision maker and the recipient was manipulated by having participants make decisions for themselves, their friend and another unknown participant. Risk preferences were closer to neutrality (i.e. more consistent with expected value) when making decisions on behalf of another participant than when making decisions for themselves or a friend. We conclude that subjective risk preferences are attenuated in surrogate decision making. Findings are discussed in relation to inconsistencies in the literature and theories of surrogate decision making.